Democracy Index and Political Culture: Bulgaria, 2017 - Blagoeva, Blaga (Research Papers, 2019)
In the article are analyzed the results from Economist Intelligence Unit’s research for Democracy Index 2017: a general presentation of the research; Bulgaria’s results according to the main criteria; Bulgaria’s political culture evaluation. The goal we set is to analyze the assessment of contemporary Bulgarian political culture in the Economist Intelligence Unit report (2017). The answer to the following question is being sought: why are Bulgaria’s contemporary political culture evaluations so low?